Monopolar and bipolar combination injuries of the clavicle: Retrospective incidence analysis and proposal of a new classification system - Bakir, M. Sinan; Carbon, Roman; Ekkernkamp, Axel; Schulz-Drost, Stefan (Journal of Clinical Medicine, 2021)
Clavicle injuries are common, but only few case reports describe combined clavicular injuries (CCI). CCI include combinations between clavicular fractures and acromioclavicular/sternoclavicular joint dislocations (SCJD). We present the first general therapeutic recommendations for CCI based on a new classification and their distribution. A retrospective, epidemiological, big data analysis was based on ICD-10 diagnoses from 2012 to 2014 provided by the German Federal Statistical Office. CCI represent 0.7% of all clavicle-related injuries (n = 814 out of 114,003). SCJD show by far the highest proportion of combination injuries (13.2% of all SCJD were part of CCI) while the proportion of CCI in relation to the other injury entities was significantly less (p < 0.023). CCIs were classified depending on (1) the polarity (monopolar type I, 92.2% versus bipolar type II, 7.8%). Monopolar type I was further differentiated depending on (2) the positional relationship between the combined injuries: Ia two injuries directly at the respective pole versus Ib with an injury at one end plus an additional midshaft clavicle fracture. Type II was further differentiated depending on (3) the injured structures: IIa ligamento-osseous, type IIb purely ligamentous (rarest with 0.6%). According to our classification, the CCI severity increases from type Ia to IIb. CCI are more important than previously believed and seen as an indication for surgery. The exclusion of further, contra-polar injuries in the event of a clavicle injury is clinically relevant and should be focused.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Acromioclavicular joint dislocation; Big data analysis; Classification system; Clavicle fracture; Clavicular combination injury; Floating clavicle; Routine data; Sternoclavicular joint dislocation